2016
DOI: 10.1002/2016gl068179
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron‐induced waves: A likely source of 150 km radar echoes and enhanced electron modes

Abstract: VHF radars near the geomagnetic equator receive coherent reflections from plasma density irregularities between 130 and 160 km in altitude during the daytime. Though researchers first discovered these 150 km echoes over 50 years ago and use them to monitor vertical plasma drifts, the underlying mechanism that creates them remains a mystery. This paper uses large‐scale kinetic simulations to show that photoelectrons can drive electron waves, which then enhance ion density irregularities that radars could observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 32 publications
(46 reference statements)
2
67
0
Order By: Relevance
“…We instead find that spectral width tends to increase with height, a feature that has been observed in incoherent scattered signals with increasing height (Chau & Kudeki, 2006). While the role of photoelectron-induced plasma waves resulting in NEIS in the 150-km region (Oppenheim & Dimant, 2016) can be understood, it was not clear as to how the plasma instability, generating FAI, sets in at the 150-km region, where neither background electric field nor plasma density gradient is significant.. Chau et al (2009) were the first to invoke the role of both NEIS and FAI in the echoing phenomenon.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…We instead find that spectral width tends to increase with height, a feature that has been observed in incoherent scattered signals with increasing height (Chau & Kudeki, 2006). While the role of photoelectron-induced plasma waves resulting in NEIS in the 150-km region (Oppenheim & Dimant, 2016) can be understood, it was not clear as to how the plasma instability, generating FAI, sets in at the 150-km region, where neither background electric field nor plasma density gradient is significant.. Chau et al (2009) were the first to invoke the role of both NEIS and FAI in the echoing phenomenon.…”
Section: Discussionmentioning
confidence: 51%
“…The ubiquitous quasiperiodicity of the echoes (e.g., Kudeki & Fawcett, 1993) and inverse relationship between echo occurrence/intensity and solar EUV flux (Patra et al, 2017) provoke us to think about the roles of atmospheric gravity waves (AGW) and low background plasma density. Patra et al (2017) have outlined a hypothesis as to how AGW in the background of low neutral and plasma density could enhance the plasma wave processes through a photoelectron pathway proposed recently by Oppenheim and Dimant (2016). Patra et al (2017) have outlined a hypothesis as to how AGW in the background of low neutral and plasma density could enhance the plasma wave processes through a photoelectron pathway proposed recently by Oppenheim and Dimant (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chau and Kudeki (2013), however, found that for perpendicular echoes, when spectral width is plotted as a function of SNR, majority of the echoes show SNR-dependent spectral width, that is, spectral width increases with SNR. This, however, by no means rule out the NEIS (Chau & Kudeki, 2013) or the recently proposed photo-electron induced plasma wave mechanism (Oppenheim & Dimant, 2016) responsible for radar echoes from the 150-km region. We find that echoes in the lower layer observed at 53 MHz clearly show spectral width linearly scaling with SNR.…”
Section: Discussionmentioning
confidence: 75%
“…These waves are predominantly generated around 150 km where most of the solar EUV flux is absorbed. Recently, Oppenheim and Dimant (2016) modeled the effect of photoelectrons on the lower F region plasma using a particle-in-cell model and suggested that photoelectrons can generate electron waves that ultimately are responsible for plasma irregularities causing the enhanced radar backscatter. This is a similar region where we observe 150-km echoes ( Figure 1).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%